The Mrs. John A. Ryerson collection relating to the Stone family of Great Britain
Correspondence and genealogical data consisting of birth and death records and lists of wills relating primarily to Andrew Stone (1703-1773), British undersecretary of state and tutor to George III, and George Stone (1708?-1764), Archbishop of Armagh, and their involvement in English and Irish politics during the 18th century. Includes material relating to Nicholas Stone (1586-1647) and his career as a sculptor and stonemason and lists of manuscript sources in Great Britain relevant to the Stone family.
Transcripts (handwritten) of materials located in British repositories and private collections.
Keywords: George -- III, -- King of Great Britain, -- 1738-1820.; Stone, Andrew, -- 1703-1773.; Stone, George, -- 1708?-1764.; Stone, Nicholas, -- 1586-1647.; Stone family; Bishops -- Northern Ireland -- Armagh; Catholic Church -- Clergy; Registers of births, etc. -- Great Britain; Registers of births, etc. -- Northern Ireland; Wills; Armagh (Northern Ireland) -- History; Great Britain -- Genealogy; Great Britain -- Politics and government -- 18th century; Ireland -- Politics and government